Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1007/s10571-021-01140-0
|View full text |Cite
|
Sign up to set email alerts
|

Elastin-Derived Peptides in the Central Nervous System: Friend or Foe

Abstract: Elastin is one of the main structural matrix proteins of the arteries, lung, cartilage, elastic ligaments, brain vessels, and skin. These elastin fibers display incredible resilience and structural stability with long half-life. However, during some physiological and pathophysiological conditions, elastin is prone to proteolytic degradation and, due to the extremely low turnover rate, its degradation is practically an irreversible and irreparable phenomenon. As a result of elastin degradation, new peptides cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 142 publications
(162 reference statements)
0
21
0
Order By: Relevance
“…An essential factor in the mechanism of action of EDPs is the peroxisome proliferator-activated receptor gamma (PPARγ) pathway, which is reported to increase the production of ROS by increasing calcium (Ca 2+ ) influx and disrupting the activity and expression of antioxidant enzymes [ 268 , 269 , 270 ]. PPARγ is reported to enhance SOD, CAT and GPx activity and increase lipid peroxidation [ 271 , 272 ]. Resveratrol, a PPAR agonist, is an example of an antioxidant compound that exerts these neuroprotective properties and was examined for its therapeutic potential in AD [ 273 , 274 ].…”
Section: Oxidative Stress In Alzheimer’s Diseasementioning
confidence: 99%
“…An essential factor in the mechanism of action of EDPs is the peroxisome proliferator-activated receptor gamma (PPARγ) pathway, which is reported to increase the production of ROS by increasing calcium (Ca 2+ ) influx and disrupting the activity and expression of antioxidant enzymes [ 268 , 269 , 270 ]. PPARγ is reported to enhance SOD, CAT and GPx activity and increase lipid peroxidation [ 271 , 272 ]. Resveratrol, a PPAR agonist, is an example of an antioxidant compound that exerts these neuroprotective properties and was examined for its therapeutic potential in AD [ 273 , 274 ].…”
Section: Oxidative Stress In Alzheimer’s Diseasementioning
confidence: 99%
“…The following is the amyloidogenic processing of the post-ischemic amyloid protein precursor that is associated with the production and deposition of amyloid in the brain following ischemia [ 67 , 68 , 69 ]. In addition, it has been shown that patients with a history of ischemic stroke have an increase in elastin-derived polypeptides in the cerebrospinal fluid that contribute to the accumulation of amyloid in the extracellular space [ 19 , 20 , 21 , 22 ]. The accumulation of amyloid in the brain after ischemia [ 67 , 70 ] and its presence in the blood [ 71 , 72 ] indicate an important role of amyloid in the progression of ischemic brain injury with Alzheimer’s disease proteinopathy.…”
Section: Amyloid Accumulation In Post-ischemic Brainmentioning
confidence: 99%
“…During post-ischemic reperfusion, neuropathological pathways include excitotoxicity, intracellular Ca 2+ accumulation, neuroinflammation, free radical and amyloid generation, modification of tau protein, necrosis, apoptosis, lipolysis, and elastin degradation to polypeptides [ 15 , 16 , 17 , 18 , 19 ]. Recently, elastin-derived polypeptides have been reported to induce overproduction of β-amyloid peptides in a model of Alzheimer’s disease [ 20 , 21 , 22 ]. Among these various neuropathological phenomena, free radical changes in brain tissue play an important role in the process of ischemic brain damage during recovery of blood flow at the primary ischemic focus.…”
Section: Introductionmentioning
confidence: 99%
“…This protein is characterized by high tolerance to mechanical damage, giving additional resistance of certain tissues. It is also a matrix for cells, especially in the nervous system [17,18]. The tropoelastin molecule is the building-block of elastin, which makes this protein nearly insoluble in water and responsible for its unique properties [19,20].…”
Section: Role Of Ros In the Origin Of Elastin-derived Peptidesmentioning
confidence: 99%
“…As described above, ROS can take part in elastin degradation directly, resulting in increased amounts of EDP protein in the organism. To date, EDPs have been well-described to cause biological effects mainly through activation of the cell receptor present naturally in the cell membrane [18,38]. EDP binds to 67-kDa elastin-binding protein (EBP), which is a catalytically inactive form of beta-galactosidase produced by alternative splicing of the GLB1 gene (Figure 2) [39,40].…”
Section: Impact Of Edps On Ros Productionmentioning
confidence: 99%